CLIL yondashuviga asoslangan biznes-tadbirkorlik ta‘limi (SCIENCE and SOCIETY, 2024)
The article discusses the implementation of the idea of developing a new type of specialist, revealing modern CLIL approaches to the organization of entrepreneurship and perspective perspectives on the development of modern entrepreneurship and educational methods of modern entrepreneurship, the principles of continuity in continuing education.